Passive daytime radiative cooling - Nurhadi Abdul Rahman (Nanyang Technological University, 2021)
The increasing effect of climate change have pushed Singapore’s weather to be significantly warmer as years passes by, boosting the use of air-conditioning units to keep the local workforce productive under hot and humid conditions. However, such conventional cooling systems are known to increase local carbon emissions, hence there was a need to explore an alternative efficient cooling technology. Passive Daytime Radiative Cooling (PDRC) is an emergent field of cooling phenomena that have gained traction in recent years. It involves the use of sunlight reflectance and heat radiation process to encourage cooling effect on the surface. Hence, the theory behind PDRC will be focused on this project, thoroughly examining its functions and theories inclusive of sunlight functions, light scattering techniques, and material structures. Our findings will primarily concentrate on the optical cooling properties of the specimens, involving the use of light scattering and heat localisation techniques to induce efficient passive and radiative cooling effects. Previous research involving the use of hydrogels and fabrication methods are greatly considered for this project. The addition of BaSO4 pigments and coloured dyes are also considered to meet research gap identified in this paper using two experimental methods: Radiative Cooling Test and Water Absorption Test. The above-mentioned experiments will be carried out to determine cooling capabilities, mechanical stability, and suitability of the specimens for outdoor environments.